Arab Berlin Dynamics of Transformation - Badr, Hanan; Samour, Nahed (Urban Studies, 2023)
Berlin is increasingly emerging as a hub of Arab intellectual life in Europe. In this first study of Arab culture to zoom in on the thriving metropolis, the contributors shed light on the dynamics of transformation with Arabs as agents, subjects, and objects of change in the spheres of politics, society and history, gender, demographics and migration, media and culture, and education and research. The kaleidoscopic character of the collection, embracing academic articles, essays, interviews and photos, reflects critical encounters in Berlin. It brings together authors from inter- and multidisciplinary fields and backgrounds and invites the readers into a much-needed conversation on contemporary transformations.